SPIRITUALITAS BISNIS: MEMPERKUAT ETIKA DAN KEBERLANJUTAN DALAM ENTREPRENEURSHIP BERDASARKAN NILAI-NILAI ALKITABIAH - Anwar Three Millenium Waruwu (SEKOLAH TINGGI TEOLOGI DAN ENTREPRENEURSHIP PRINGGADING (STEP) SEMARANG, 2024)
The development of entrepreneurship based on Alkitabian values has become increasingly crucial amidst modern society plagued by social inequality and economic instability. This article aims to investigate the contribution of Alkitabian entrepreneurship as a solution to these issues. Highlighting the decline in poverty rates but the widening economic disparity in Indonesia, this research demonstrates that micro and small enterprises grounded in Alkitabian values can rectify social disparities and advance well-being. A qualitative research method with a literature review approach is employed to gain a profound understanding of the implementation of Alkitabian values in entrepreneurship and their impact on business sustainability and society. The research findings indicate that Alkitabian entrepreneurs, guided by values such as honesty and justice, are capable of creating a business environment that is fair, inclusive, and sustainable. Furthermore, social responsibility is integral to this business model, with a focus on community empowerment and positive contributions to society. This study details how Alkitabian values can serve as a foundation for building entrepreneurial solutions that positively impact collective well-being in the complex economic context. Keywords: Alkitabiah Entrepreneurship, Social Inequality, Business Sustainability, Social Responsibility.